ORGANIZATION OF INTERNAL AUDIT QUALITY CONTROL AND ITS IMPROVEMENT - Tagirovna, Minutdinova Liliya; Alimovich, Masharipov Ozod (Research Parks Publishers, 2023)
This article reveals the key problems that arise in the process of organizing internal audit quality control, conducts a deep analysis of the principles, procedures, methods, and presents the main directions of audit quality control. An analysis of the audit quality indicators that are available in the quality control system indicates that all of them are insufficiently disclosed and need to be clarified. The structure of the audit quality control system at the enterprise has been developed, its content has been disclosed. The regulation of internal quality control of the audit organization, which reveals the quality control procedures, is disclosed. The introduction of an improved system of internal audit quality control will minimize the costs of organizing this process in each audit organization, will provide confidence to clients that the audit organization acted within the established standards and principles.